THE BANK LENDING CHANNEL OF MONETARY POLICY TRANSMISSION IN A DUAL BANKING SYSTEM - H. Ibrahim, Mansor (Journal of Islamic Monetary Economics and Finance, 2017)
This paper examines the impact of monetary policy on bank lending in a dual banking system, i.e. Malaysia. Making use of an unbalanced panel data set of 38 Islamic and conventional banks covering mostly 2001-2014, we find evidence that variations in monetary policy affect lending growth of Islamic banks and, to some extent, conventional banks. The results further reveal that, in conformity with studies using aggregate Islamic financing data, the Islamic financing growth reacts more strongly to monetary policy changes. Moreover, we find no marked difference between full-fledged Islamic banks and Islamic bank subsidiaries in their responses to monetary policy. While we also document some evidence indicating the significant relations between bank-specific variables and lending growth, the bank-specific variables do not seem to have any role in impacting the potency of the bank lending channel. Finally, we find that lending growth is directly related to economic growth, suggesting procyclicality of bank lending/financing in Malaysia. These results have important implications for effective implementation of monetary policy and further development of Islamic banks in Malaysia.